(untitled) (El Hilo de la Fabula, 2024)
A comprehensive essay with a multiplicity of axes. Different tipes of autobiofictional writing are highlighted, forming a loose corpus through which detailed analysis is activated. It is of interest as a reference text due to its conceptual vision and expository clarity.